VIP-, substance P- and met-enkephalin-immunoreactive innervation of the human gastroduodenal mucosa and Brunner's glands. Issue 9 (September 1984) - Ferri, G L; Botti, P; Biliotti, G; Rebecchi, L; Bloom, S R; Tonelli, L; Labò, G; Polak, J M
Abstract : VIP-, substance P- and met-enkephalin-containing innervation of the human gastroduodenal mucosa and Brunner's glands was studied by immunocytochemistry on whole mount tissue preparations. A dense VIP-containing nerve supply was found around fundic and pyloric glands, while the few and scattered substance P-immunoreactive fibres tended to run across the full thickness of the gastric mucosa. In the duodenum, both VIP and substance P were present in a striking nerve network in the villi as well as in the muscularis mucosae and around blood vessels. Both peptides were also immunostained in nerve bundles and neuronal perikarya between the lobules of Brunner's glands, while only very few fibres reached the proximity of acinar cells. Met-enkephalin-immunoreactivity was detected in a small number of nerve fibres, virtually confined to the basal parts of the mucosa and to the duodenal submucous plexus.